Implementasi Program Beasiswa Sepuluh Sarjana PerDesa Menuju Sumber Daya Manusia Unggul di Kecamatan Kepohbaru Kabupaten Bojonegoro - Kurniawan, Ferdy Anton Adit; Tauran; Rahaju, Tjitjik; Prabawati, Indah (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
The Ten Scholars per Village Scholarship Program is one of the flagship policy initiatives of the Bojonegoro Regency Government, providing educational financial assistance to ten students from each village to pursue higher education at public or private universities in Bojonegoro. This program was designed as a strategic effort to address the low proportion of the population attaining higher education. In addition, the policy aims to improve the quality of human resources and to enhance the Human Development Index (HDI) of Bojonegoro Regency. However, in its implementation, several challenges have been identified, including administrative requirements that hinder prospective beneficiaries, underutilization of allocated funds, and low public interest—particularly in Kepohbaru District—in pursuing higher education. This study aims to describe the implementation of the Ten Scholars per Village Scholarship Program in Kepohbaru District, Bojonegoro Regency. The research employs a qualitative approach with a descriptive research design. The analytical framework is based on the policy implementation model proposed by Donald Van Meter and Carl Van Horn, which identifies six key indicators influencing policy implementation success: (1) policy standards and objectives, (2) resources, (3) characteristics of implementing agencies, (4) dispositions or tendencies of implementers, (5) inter-organizational communication and implementation activities, and (6) economic, social, and political environments. The findings indicate that the implementation of the program in Kepohbaru District has not been fully optimal. Significant obstacles were identified, particularly in the aspects of communication and the socio-economic environment. In terms of communication, program socialization has not reached all segments of the community evenly. Meanwhile, from a socio-economic perspective, a prevailing perception exists that entering the workforce offers a faster path to success than pursuing higher education. This condition is further exacerbated by weak motivational support, resulting in scholarship information being largely overlooked and the program not being utilized to its full potential. Consequently, a gap has emerged between the substantial budget allocation and the actual number of beneficiaries at the local level.